Pembaruan sistem pendidikan Islam: Sekolah Islam Terpadu - Frandani, Muhammad (Program Studi Magister Pendidikan Agama Islam, 2023)
If compared, Islamic education in Indonesia is like a train that has been running on a track for a very long time, passing through cool and hot nature. traversing steep valleys, pitch-dark jungles, and various obstacles, as forges for the path of Islamic education in the archipelago. When talking about the modernization of Islamic education, experts focus more on three objects of study, namely Islamic boarding schools, madrasas, and tertiary institutions. Meanwhile, school brands do not get a major place among Islamic education researchers. Only a few researchers or educational thinkers have a focus on Islamic educational institutions called schools. So it becomes interesting when there is a study related to the Integrated Islamic School (SIT), so that various efforts of